2010
DOI: 10.1038/sj.bjc.6605839
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of CD147 (EMMPRIN), CD44v3-10, MDR1 and monocarboxylate transporters is associated with prostate cancer drug resistance and progression

Abstract: Background:The aim of this study is to seek an association between markers of metastatic potential, drug resistance-related protein and monocarboxylate transporters in prostate cancer (CaP).Methods:We evaluated the expression of invasive markers (CD147, CD44v3-10), drug-resistance protein (MDR1) and monocarboxylate transporters (MCT1 and MCT4) in CaP metastatic cell lines and CaP tissue microarrays (n=140) by immunostaining. The co-expression of CD147 and CD44v3-10 with that of MDR1, MCT1 and MCT4 in CaP cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 49 publications
8
86
2
Order By: Relevance
“…Our flow cytometry results showed much higher expression level of CD147 in CSC-like cells than in NCSCs. Hao et al and Slomiany et al studied CD147 and CD44 expression levels in breast CSCs and found both CD147 and CD44 enriched in CSCs (37)(38)(39). Similar results were observed in our studies.…”
Section: Discussionsupporting
confidence: 82%
“…Our flow cytometry results showed much higher expression level of CD147 in CSC-like cells than in NCSCs. Hao et al and Slomiany et al studied CD147 and CD44 expression levels in breast CSCs and found both CD147 and CD44 enriched in CSCs (37)(38)(39). Similar results were observed in our studies.…”
Section: Discussionsupporting
confidence: 82%
“…Overexpression of CD44v3-10, MDR1 and MCT4 was found in most primary prostate cancer tissues, and was significantly associated with prostate cancer progression (29). Another study indicated that the overexpression of CD147, MCT1 and MCT4 is correlated with the progression of epithelial ovarian cancer (EOC) (30).…”
Section: Discussionmentioning
confidence: 95%
“…MDR1/P-glycoprotein or ABCB1 is one of the well characterized members of the energy-dependent drug efflux pumps that reduce intracellular accumulation of anticancer drugs, leading to the MDR phenotype [26]. Recent studies have demonstrated the co-localization of CD147 with MDR1, highlighting the possible cooperative roles of these molecules in cancer drug resistance and progression [27,28]. In fact, increased expression of CD147 stimulates hyaluronan production, with MDR being induced in a hyaluronan-dependent manner [29,30].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%